2012
DOI: 10.1038/nprot.2011.438
|View full text |Cite
|
Sign up to set email alerts
|

Intravital multiphoton imaging of immune responses in the mouse ear skin

Abstract: Multiphoton (MP) microscopy enables the direct in vivo visualization, with high spatial and temporal resolution, of fluorescently tagged immune cells, extracellular matrix and vasculature in tissues. This approach, therefore, represents a powerful alternative to traditional methods of assessing immune cell function in the skin, which are mainly based on flow cytometry and histology. Here we provide a step-by-step protocol describing experimental procedures for intravital MP imaging of the mouse ear skin, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 41 publications
2
149
0
Order By: Relevance
“…The mouse ear was imaged as previously described. 41,42 The anesthetized mouse was mounted on a homemade holder. 41,43 The mice were then disposed on the stage of an upright Leica SP5X MP (Leica microsystems) and the temperature was set at 28 C for preserving the mouse body temperature around 37 C. A single excitation wavelength at 940 nm (Chameleon Ultra II, Coherent) was used for 2PEM and recorded using a 25x 0.95 N.A.…”
Section: -Photon-excitation Microscopy (2pem) Imagingmentioning
confidence: 99%
“…The mouse ear was imaged as previously described. 41,42 The anesthetized mouse was mounted on a homemade holder. 41,43 The mice were then disposed on the stage of an upright Leica SP5X MP (Leica microsystems) and the temperature was set at 28 C for preserving the mouse body temperature around 37 C. A single excitation wavelength at 940 nm (Chameleon Ultra II, Coherent) was used for 2PEM and recorded using a 25x 0.95 N.A.…”
Section: -Photon-excitation Microscopy (2pem) Imagingmentioning
confidence: 99%
“…However, intravital imaging in mice has limited temporal and spatial resolution and often requires invasive surgical procedures (Goodarzi et al, 2003). The recent improvements using intravital imaging of inflammation in the ear of mice in vivo (Li et al, 2012) has minimized the preparation time and increased the resolution, but still requires invasive procedures. By contrast, zebrafish are transparent during embryonic development and provide a non-invasive platform to observe leukocyte behavior and subcellular molecular events at a high resolution in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have observed that pigmented tissues and cells are highly sensitive to MP illumination due to their high MP absorption, and contribute to the generation of non-specific high intensity signals ("speckling") (Ng et al 2011;Li et al 2012). This speckling not only compromises the image quality, but also induces heat injury that can trigger an inflammatory response and severely damage the tissue.…”
Section: Choice Of Tumor Modelsmentioning
confidence: 99%
“…Although all myeloid cells in these mice express GFP, neutrophils express the highest amount of the fluorescent protein (Ng et al 2011), which makes them distinguishable from monocytes or macrophages based on the fluorescent intensity and cell morphology. To visualize blood vessels, quantum dots, fluorescent dextrans and lectins or Evans blue dye can be injected intravenously (Ng et al 2011;Hickman et al 2009;Germain et al 2006;Li et al 2012). Furthermore, changes in the extracellular matrix within tumors can be monitored by second and third harmonic generation signals (Friedl et al 2007).…”
Section: Visualizing Neutrophils Blood Vessels and Extracellular Matmentioning
confidence: 99%